Depression, Pharmacotherapy, and the Demand for a Novel Health Product - Manuela Angelucci; Daniel M Bennett (Institute of Labor Economics (IZA), 2022)
Depression, a common and serious illness that is more prevalent among the poor, may limit the demand for health products and other beneficial technologies. To investigate, we evaluate the impact of depression treatment on the demand for a novel health product, hand sanitizer, in India. We cross-randomize depression treatment (pharmacotherapy) and free distribution of the product, and measure impacts on subsequent willingness to pay using the Becker-Degroot-Marschak mechanism, as well as product use. Depression treatment improves mental health and increases willingness to pay by 5 percent, implying that having major depression reduces willingness to pay by 26 percent. However, depression treatment does not affect product use, which is high after free distribution for all recipients. We investigate several pathways that may explain this pattern. These results are consistent with an effect of depression on the decision costs associated with a novel purchase. Our findings suggest that policymakers should use free distribution and other approaches that minimize decision costs to encourage the adoption of health products in high-depression settings.
Keywords: I15; I18; 330; depression; health; poverty